Tuberculous osteomyelitis in an immunocompetent patient with miliary tuberculosis - Gunawan Gunawan; A Harahap; Bambang Setiyohadi; Cleopas Martin Rumende (Indonesian Rheumatology Association, 2010)
Osteomyelitis is an infection of the bone, which may be caused by direct pathogen inoculation following trauma of surgery, contiguous spread from adjacent soft tissue or joint, or hematogenous spread from a focus of infection. Hematogenous osteomyelitis accounts for 20% of all cases of osteomyelitis.1 This type of osteomyelitis most often affect the long bones and vertebrae, although it could also affect other sites such as pelvic bones or clavicle.1 Mycobacterium tuberculosis is one of the causes of hematogenous osteomyelitis,comprising of 10 to 35 percent of extrapulmonary tuberculosis, or 2% of all tuberculosis cases.2,3 Joint involvement, when occur, is usually monoarticular, and mainly affect the weight-bearing joints such as hip or knee. Polyarticular cases occur in 10– 15% of extrapulmonary tuberculosis cases in developing countries.4 Tuberculous osteomyelitiscases are reported to be decreasing in number, probably because of earlier diagnosis and promptmanagement. In this article we report a case oftuberculous osteomyelitis in a patient with miliary tuberculosis